The Triangle Balance of Public Service: Basic Rights Applicative for Workers - Suci Flambonita; Vera Novianti; ahmaturrahman Ahmaturrahman (Universitas Sriwijaya, 2024)
The mission of the state, as stipulated by the constitution, is to accomplish social welfare, as stated in the fourth paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia, which serves as the foundation for the Indonesian country to operate as a National Development Document. As a result, state administrators are now required to strive for public welfare, including state-provided facilities, such as public services, whose service requirements must be met in line with statutory regulations. Public Services are one of the eight areas of change in the implementation of bureaucratic reform in the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 25 of 2020 concerning the Road Map for Bureaucratic Reform 2020-2024. The 8 (eight) areas of change in bureaucratic reform are as follows: (1) Change management; (2) Policy Deregulation; (3) Organizational Structuring; (4) Management Arrangement; (5) Arrangement of HR Apparatus; (6) Strengthening Accountability; (7) Strengthening Supervision; and (8) Improving the Quality of Public Services. The method utilized for analyzing the issue is a combination of normative and empirical, with approaches including the statutory approach, conceptual approach, and case approach. The discussion in this article is based on the Public Services Law, which declares that every public service provider is required to deliver quality services to all users. Lactation rooms for breastfeeding mothers and toddlers are one of the features that help to make inclusive courts a reality. Lactation rooms in workplaces and public facilities are also protected by the Minister of Health of the Republic of Indonesia's Regulation No. 15 of 2013 on Procedures for Providing Special Facilities for Breastfeeding and/or Expression of Breast Milk. This regulation is, of course, inextricably linked to Law Number 36 of 2009 concerning Health, particularly Article 128, which governs babies' right to receive exclusive breast milk from birth for 6 (six) months, as emphasized in Palembang City Regional Regulation No. 2 of 2014 concerning the Provision of Exclusive Breast Milk. As a result, the study's findings suggest that several colleges in Palembang City do not provide lactation rooms for breastfeeding moms, instead offering only locked rooms, making it uncomfortable for working women who bring their newborns to work. As a result, this does not meet the requirements of public services for breastfeeding.